Sustainable shrimp farming in Sri Lanka; Utilization of BMPs and antibiotics use (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: In the context of the fast-expanding shrimp farming industry in Sri Lanka, this study aimed to evaluate the distribution and understanding of BMPs, examine the relationship between BMPs and disease outbreaks, and analyze the current antibiotic usage trends through a fact-finding survey. Materials and Methods: A questionnaire survey was conducted in 131 shrimp farms located in Puttalam District in North Western Province, where shrimp farming is thriving in Sri Lanka. The survey was conducted from September to October 2021. In addition, in August 2022 and August 2023, interviews were conducted with shrimp farms in Puttalam district and Batticaloa district, shrimp hatcheries, and export companies. Data were analyzed using descriptive statistics, Probit, and Tobit regression analysis. Results: The item-count technique revealed a significant (p < 0.05) difference in the use of antibiotics without consulting experts, signifying inappropriate use. No aquaculture farmer reported being unaware of BMPs, and among the 45 farmers who attended a BMPs seminar, 30 claimed to possess a good understanding of BMPs. Probit and Tobit regression results revealed that the rate of understanding of BMPs, education level, and obtaining information on the sanitation management of shrimp farming from extension and guidance organizations were inversely associated with both disease incidence in shrimp farming and shrimp discards. Conclusion: Although the use of antibiotics is prohibited in BMPs, the analysis results suggest inappropriate use of antibiotics. The findings indicate that enhanced BMP understanding can reduce disease incidence and shrimp discards, emphasizing the need for incentives to promote BMP adoption and reduce the necessity for antibiotics.Adv. Vet. Anim. Res., 11(1): 33-39, March 2024http://doi.org/10.5455/javar.2024.k744